Cumulative Health Drivers of Overnight Hospitalization for Australian Working-Age Adults Living Alone: The Early Warning Potential of Functionality - John, Rodwell (My University, 2022)
There is a need to better understand the drivers of hospital utilization for the large and growing number of adults living alone. The cumulative effect of health drivers can be assessed by initially considering clinically advised information, then considering issues that a general practitioner or the person themselves may know. Logistic regression analyses were conducted on longitudinal data from the Household, Income, and Labor Dynamics in Australia (HILDA) survey with three time points over four years (n = 1019). The significant predictors of overnight hospitalization were the presence of a long-term health condition (Time 1), hospitalization severity and comorbidity (Time 1), work ability (Time 2), physical functioning (Time 2), being separated/divorced and having one or more health care cards. Health issues were predictive up to four years before the hospitalization window. That baseline risk of hospitalization was modified as symptoms and relatively salient changes in functionality accumulated. Specific sub-groups of hospital users had access due to insurance or special coverage. The impact of living alone on hospitalization may be able to be partly addressed through interventions such as improving access to primary care and using early warning triggers such as decreasing functionality to seek primary care before seeking hospitalization.
International Journal of Environmental Research and Public Health
Keywords: Ageing; Disadvantage, adversity and resilience; Health and wellbeing